Hubungan Frekuensi Hemodialisis dengan Tingkat Stres pada Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisis - Fitri Rahayu; Topan Fernandoz; Rafika Ramlis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study was to determine whether there is a correlation between hemodialysis frequency and stress level in chronic renal failure patients undergoing hemodialysis at the Hemodialysis Installation of RSUD Dr. M. Yunus Bengkulu City in 2016. The research design used by researchers was a descriptive analytic method, namely research that aims to explain each of the variables studied. The results showed that of 58 respondents with frequency of hemodialysis, there were often 28 respondents (48.3%) with moderate stress levels, 17 respondents (29.3%) with mild stress levels, and there were 13 respondents (22.4 %) with a high stress level while from 9 respondents with hemodialysis frequency there were not often 5 respondents (55.6%) with mild stress levels, 3 respondents (33.3%) with moderate stress levels and 1 respondent (11 , 1) with a mild stress level. Conclusion, There is a significant relationship between HD frequency and stress level in CKD patients at the Hemodialysis installation at RSUD Dr. M. Yunus Bengkulu. Keywords: Frequency, Hemodialysis, Stress Level